DRAMATIC ELEMENTS IN DASHNER’S MAZE RUNNER NOVEL AND FILM ADAPTATION - Anggia Putria; Muizzu Nurhadi (Anaphora : Journal of Language, Literary, and Cultural Studies, 2019)
The research aims to reveal how the application of dramatic elements of Dashner’s Maze Runner is transformed into its film adaptation. To achieve the purpose, the researcher analyzes seven dramatic elements by Gustav Freytag’s Pyramid which consist of exposition, inciting moment, rising action, climax, falling action, resolution, and denouement. This research uses the descriptive qualitative method. The results of this research are the differences of the dramatic elements in the novel and film adaptation are not significant because only the scenes of exposition and rising action are not similar.